Service Quality in the Telecommunication Industry: Analysis with Special Reference to DSL Services - Rajeswari, S.; Srinivasulu, Yarlagadda; Thiyagarajan, S. (Indian Journal of Marketing, 2016)
The research study was conducted to analyze the service quality in the telecommunication sector because in the present intensive broadband market, the survival of wire line telecommunication sector depends on the service quality offered to the end user that serves as a key tool for competition and survival. Though there exist various constructs to measure service quality, the study used performance items of service quality, and survey method was used to collect data from the sample. Based on the analysis, the tiered classification of service quality was represented, which gave a clear scheme for the telecom service providers to identify the service quality attributes that leads to enhancement in their performance in a highly competitive market.